The Utilization Of Beehive Wax a Combination of Nutmeg Extract (Myristica fragrans Houtt.) and Langsat (Lansium domesticum L.) as Aromatherapy and Mosquito Repellent - Thesia Megi Kurniawati Rettob; Edieli Zebua; Ilham Saputra Butar-butar; Febiola Gabriela Tular; Yermia S. Mokosuli (Jurnal Biologi Tropis, 2021)
Mosquitoes often being the vector of some diseases, such as dengue hemorrhagic fever. To prevent these diseases vectored by mosquitoes, we could use mosquito repellent. But based on some research, these mosquito repellents on the market contain some dangerous chemicals, for example, Dichlorvos, Porpoxure, and synthetic pyrethroid. These kinds of chemicals can cause some side effects that are not good for health, ranging from headaches, nausea, to cancer and organ dysfunction. Therefore, it is necessary to have a mosquito repellent that is safer for health with minimal side effects. This research is an experimental type of research that aimed to determine the effectiveness of anti-mosquito in the form of an aromatherapy candle made of the beehive with the consistency of pala pulp extract and langsat seed extract. Pala pulp extract and langsat seed extract were obtained from the maceration method and then processed by Rotary Evaporator.ÃÂ  The concentrations used are Pala pulp extract: langsat seed extract. I: 0,5gr:0,25gr, II: 5gr:2,5gr. Both of the concentrations will be blend into 200gr of solid candle that will be melt. A test was made on some adult mosquitoes. Mosquitoes are being bred. The mosquitoes were placed on a cage that had been build by the researchers first. The measurement scale on this research is the mortality rate of the mosquitoes counted from the second we light up the anti-mosquito aromatherapy candle. There are two types of data analysis on this research, includes the anti-mosquito test and organoleptic test. The first concentration test's result shows that there is a very minimal effect on the mosquitoes. when the test was run, there were five adult mosquitoes inside the cage, an observation was done for 10 minutes counted from the time the candle was lit up. At the first 2 minutes 10 seconds, there is 1 mosquito that died, and the rest of the time for 10 minutes there was no other ÃÂ mosquito died. The second concentration test's result shows a really big impact on the mortality rate of the mosquito. There were seven adult mosquitoes inside the cage when the test was run. And for 10 minutes, 6 mosquitos died. This means that the second concentration was the most effective amount of the concentration to apply on the candle. Hopefully, the result of this research could be useful for society in terms of environment-friendly anti- mosquito usage.